The relative age effect at the ice hockey world championships (IHWC) in the years 2015-2017 - Nykodým, J.; Bozdech, M.; Agricola, A.; Zhánel, J. (Journal of Human Kinetics, 2020)
The relative age effect (RAE) theory is based on the premise that athletes born in the first months of the calendar year have a significant probability of a higher level of physiological, morphological and psychological abilities compared to later-born athletes. The aim of our study was to verify the influence of the RAE on adult ice hockey players, specifically Ice Hockey World Championships` (IHWC) participants in the years 2015-2017 (n = 1,200). Based on the chi-squared (Chi2) analysis, the influence of the RAE during the 2015-2017 period could not be rejected for all observed players (Chi2 = 54.6, p < 0.01, w = 0.21) or for all the players for particular years (2015, 2016, and 2017; p < 0.01). During the monitored period (2015-2017), the RAE could not be rejected for any player`s position (forward, defender, or goaltender). Based on the effect size analysis (Cohen`s w), the strongest RAE was observed among goaltenders (w = 0.31), then forwards (w = 0.24) and finally defenders (w = 0.15). The assessment of player`s positions in particular years showed statistical significance for goaltenders only in 2015 (Chi2 = 11.3, p < 0.05). With regard to forwards, significance was confirmed for 2015 (Chi2 = 8.5, p < 0.05), 2016 (Chi2 = 15.2, p < 0.01) and 2017 (Chi2 = 14.3, p < 0.01). Therefore, the presence of the RAE could not be rejected for all these cases. The results of the research show that members of national teams in the years 2015-2017 were players who were chronologically older, which is consistent with the results of other authors addressing the RAE.